Organization of Nursing work regarding the integration of family care for hospitalized children - Silva, Janaína Lopes da; Santos, Emelynne Gabrielly de Oliveira; Rocha, Cintia Capistrano Teixeira; Valença, Cecília Nogueira; Júnior, Osvaldo de Góes Bay (Rev Rene, 2015)
Objective: to discuss the organization of Nursing technician’s work in the interface of the care of family members of hospitalized children and to identify their perception of the insertion of family in caring for this child. Methods: this is an exploratory descriptive study with a qualitative approach, undertaken in the pediatric inpatient unit of a university hospital with six Nursing technicians, through semi-structured interviews. Results: professionals realized the importance of the family’s presence for the child’s recovery; however, in basic care which was previously developed by Nursing, they were eventually delegated to be companions, with care for the child-family binomial forgotten by the professional. Conclusion: nursing technicians recognize the benefits and difficulties of the presence of a companion. However, it is perceived that there was a lack of professional preparation when considering the binomial of child-family during hospitalization.